Development of Cross-Sector Dialogues on Ethics: A Field Study with Global Application. (1st October 2016) - Prysmakova, Palina; Smith, Robert W.
Abstract : This article explores how relations between non-governmental (NGO) and civil society (CSO) organizations and the government allow these entities to promote ethical behavior in public administration. It postulates that NGOs and CSOs are in the best position to embrace the demand-side approach to ethics reform precisely because of their ability to create a cross-sector dialogue on the imperative of ethics in government. Using insights gained from examining three countries in Central and Eastern Europe, the article develops a conceptual framework for understanding the interrelationships and value of the networks that foster ethical dialogue. The robust fieldwork approach reveals important observations that inform a framework for the balanced supply-demand continuum that promotes long-term success of ethics improvement. The proposed framework holds great utility as both a descriptive and an evaluative means to compare ethics reforms across the globe.